Effects of Predictive Nursing Intervention among Patients with Acute Stroke - Lina Gong; Chunhong Ruan; Xuan Yang; Wanli Lin (Iranian Journal of Public Health, 2021)
Background: To explore the effects of predictive nursing intervention among patients with acute stroke.